Spatial extent of the North American Monsoon: Increased cross-regional linkages via atmospheric pathways (2009)
ABSTRACT: The North American monsoon is a key featureaffecting summer climate over Southwestern NorthAmerica. During the monsoon, evapotranspiration fromthe Southwest promotes transference of water to theatmosphere which is subsequently distributed across thecontinent - linking the SW to other regions via atmospherichydrologic connectivity. However, the degree to whichatmospheric connectivity redistributes monsoonal terrestrialmoisture throughout the continent and its sensitivity toclimate disturbances such as drought is uncertain. Wetracked the trajectory of moisture evapotranspired within thesemiarid Southwest during the monsoon season using aLagrangian analytical model. Southwest moisture wasadvected north-east accounting for 15% of precipitationin adjacent Great Plains regions. During recent drought(2000–2003), this amount decreased by 45%. Our resultsillustrate that the spatial extent of the North Americanmonsoon is larger than normally considered when accountingfor hydrologic connectivity via soil moisture redistributionthrough atmospheric pathways.